Modern Algoritm for the Treatment of Stenotic Laryngitis in Children - O. I. Lekomtseva; T. A. Britkova; S. V. Andreeva (LLC "Diagnostics and Vaccines", 2016)
This article presents the own results of the introduction the algorithm for the treatment of stenotic laryngotracheitis in children. This contributed to the rapid recovery of patients, prevention of nosocomial infections, as well as a significant reduction in the volume of therapeutic interventions.